The asymmetric synthesis of arylglycines - Hendrix, James A., author; Williams, Robert M., advisor (Colorado State University. Libraries, 1992)
The asymmetric synthesis of several arylglycines is discussed. Several methods for the coupling of an aromatic group to the chiral bromoglycinates (171, 172) were developed. It was found that the cuprate and Friedel-Crafts couplings provided the desired aryl-coupled glycinates in the greatest yield with excellent selectivity. An oxidative protocol was employed to unmask the oxazinone chiral auxiliary which provided the desired free α-amino acids. A reductive deprotection method was also employed in two unique cases which efficiently gave the arylglycine products. The % ee's ranged from 82 to 94 %. This methodology was further utilized in an approach to the asymmetric synthesis of the bis-arylglycine, actinoidic acid. This study explored the scope of the Stille biphenyl cross-coupling reaction and produced methodology for the synthesis of biphenyl amino acid precursors.
Keywords: Amino acids -- Synthesis; Asymmetric synthesis; Glycine